The influence of the discovery learning model on students' mathematical creative thinking abilities in class VIII of SMP Negeri 1 Pematangsiantar - Ana Tasya Grace Adelina Sidabutar; Lois Oinike Tambunan; Yoel Octobe Purba (Lembaga Riset Mutiara Akbar, 2026)
This study aims to analyze the effect of the Discovery Learning learning model on the mathematical creative thinking ability of eighth grade students of SMP Negeri 1 Pematangsiantar. The study used a quantitative approach with a One-Shot Case Study design. The research sample consisted of 30 students selected through cluster random sampling techniques. Data were collected through a mathematical creative thinking ability test and a student perception questionnaire, which have been declared valid and reliable. Data analysis included normality and linearity tests, as well as hypothesis testing using simple linear regression and t-test. The results showed that the Discovery Learning model had a positive and significant effect on students' mathematical creative thinking ability, with a regression equation of Y = 9.100 + 0.313X. The significance value of 0.000 is less than 0.05 and the calculated t value (11.987) is more than the t table (2.048). The coefficient of determination of 83.7% indicates a very strong contribution. Thus, the Discovery Learning model is effective in improving students' mathematical creative thinking ability.